DINAMIKA PEMBELAJARAN GEOGRAFI DI SMAN 9 TAKALAR SULAWESI SELATAN - Erman Syarif (Center of Language and Cultural Studies, 2018)
The purposes of this study are to identify the dynamics of geography learning in SMA Negeri 9 Takalar, and to describe what factors are to be supporters of the quality of geography learning in SMA Negeri 9 Takalar. This study used a qualitative approach involving teachers at SMAN 1 Takalar as informants. The results showed that the dynamics of learning geography are of less conducive in terms a) learners are less involved in the learning process, b) teachers of geography subject facilitate and motivate learners in the learning process at the minimum degree, c) the teachers do not develop models of innovative learning, and d) in the learning process, teachers rely much on teacher-centered approach. In addition, factors supporting the quality of learning of geography comprise of a) teachers and learners collaborate for the achievement of improved learning outcomes, b) multiple sources a reading and video learning about learning models and developed in geography learning have been used, and c) the teacher is able to understand the characteristics of learners by using a learning model in variety and innovative manners.